Foto uit het boek "Het rijke onvermogen. Een fotoreportage over West-Duitsland" (201/118). Zie ook BG C14/41 - Alphen, Oscar van
Foto uit het boek "Het rijke onvermogen. Een fotoreportage over West-Duitsland" (201/118). Zie ook BG C14/41.